Soft skill communication and prospective bachelor - Mazdalifah; Lubis, Fatma Wardy; Masril, Munzaimah (Talenta Publisher, 2020)
Soft Skill communication skills are very important for prospective scholars. These abilities are useful in dealing with the world of work, such as during interviews, convey ideas well, and are able to negotiate and looby. The training was attended by 150 participants from various faculties at the University of North Sumatra such as: Faculty of Mathematics and Natural Sciences, Faculty of Economics, Faculty of Engineering, Faculty of Agriculture, Faculty of Law, Faculty of Cultural Sciences. The training method uses the method of delivering two-way communication and material simulation. The result of this community service activity is the increased knowledge and skills of Soft Skill Communication candidates for the University Sumatra Utara candidate in the face of the workforce.